The effects of different surgical approaches on the psychological status, medical coping mode and quality of life of patients with lung cancer - Chen, Yi-ping; Zhang, Yi; Chen, Xing; Luo, Jiang; Chen, Zhangqun; Zhao, Liping; Xia, Guili; Sui, Xueqi; Li, Yunchen (Frontiers in Psychology, 2023)
Objective: To compare the effects of robotic-assisted thoracic surgery (RATS), video-assisted thoracic surgery (VATS) and thoracotomy on the psychological status, medical coping mode and quality of life of lung cancer patients. Methods: 158 lung cancer patients were selected in a thoracic surgery center of a third-grade hospital in Hunan Province, China, from September 2020 to November 2020. The Self-Rating Anxiety Scale, Self-Rating Depression Scale, Medical Coping Modes Questionnaire and SF-36 were used to assess the effects of different surgical approaches on patients. T-test and analysis of variance were adopted to analyse the data. Results: Results revealed the depression score of patients was increased and their short-term quality of life was decreased, they inclined to adopt positive coping mode after surgery (p<0.05). The RATS group and the VATS group only differ in the scores of avoidance dimension of medical coping modes (p＜0.05). The VATS group and the thoracotomy group only differ in the scores of body pain dimension of quality of life (p＜0.05). Different surgical approaches had no effect on the scores of psychological status, medical coping modes except avoidance dimension and quality of life except body pain dimension of patients with lung cancer (p＞0.05). Conclusions:There was little effects of different surgical approaches on the lung cancer patients’ psychological status, medical coping modes and quality of life, but the depression of patients increased and their quality of life decreased after surgery.